Design of Compact Circularly-Polarized and Broadband Slot-Loaded Microstrip Patch Antenna - Fang Yang; Mingfei Wei; Min Wang; Chun Wang; Junni Zhou (Dianxin kexue)
The design method of a compact cross slot broadband or and circularly polarized microstrip patch antenna was presented.A wide cross-shaped slot was embedded on the square patch for size reduction.The substrate was a stacked structure of an FR4 and an air layer.An L-shaped strip was added in the slot and only by changing the feeding point on the strip,circular polarization or broad impedance bandwidth can be obtained.ANSYS HFSS simulation results show that the circular polarization bandwidth（AR≤3 dB）and impedance bandwidth（VSWR≤2） were 1.7% and 5.8%,respectively.The antenna had stable power gain within a broad bandwidth and its peak power gain was 7.8 dB.Meanwhile,52.3% patch area reduction can be achieved.The impedance bandwidth can be improved to 9.4 % by varying the feeding location and adjusting the two resonance frequencies of the antenna.Compared with traditional microstrip patch antennas,the impedance bandwidth was improved 114%.